Portfolio Assessment Based Numbered Head Together Toward Students’ Knowledge Competency of Mathematics - Purwatiningsih, Ni Luh Dian; Wulandari, I Gusti Agung Ayu (Jurnal Ilmiah Sekolah Dasar, 2020)
The low competency of students' mathematical knowledge is caused by the lack of optimal models during learning so the students find it difficult to understand learning. It was proven by the results of observations, 53 students or 21.73% of Mathematics PTS scores had reached KKM while as many as 191 people or 78.27% had not yet reached the KKM. This study aimed at analyzing the effect of the NHT model based on portfolio assessment on the competency of the fifth-grade elementary school. This research was a quasi-experimental study with a non-equivalent control group design. The population was all grade V elementary schools consisting of 10 classes of 244 students. The sample was determined using a random sampling technique so selected the fifth grade (Elementary School) SD 1 Mengwi of 34 students as the experimental group and the fifth grade Elementary School Mengwi of 35 students as a control group. In the process of data collection, the test was chosen as a research instrument in the form of an ordinary multiple-choice objective test so the obtained data in the form of mathematical knowledge competency values in the form of quantitative data, then it was analyzed using uji-t analysis with the polled variance formula. The results of data analysis obtained tcount = 4.351> ttable = 2,000 (α = 0.05 and dk = 67) then H0 was rejected and Ha was accepted, which means that there are significant differences between the experimental and control groups. Based on these results, it can be concluded that the NHT model based on portfolio assessment influences the competency of mathematics knowledge in the fifth-grade elementary school.